Non-stationary heat transfer in two-phase hollow cylinder with functionally graded effective material properties with second kind of boundary conditions = Niestacjonarny przepływ ciepła w przewodniku cylindrycznym z warunkami brzegowymi drugiego rodzaju - Ostrowski, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The unidirectional non-stationary heat conduction in two-phase hollow cylinder is considered. The conductor is made of two-phase stratified composites and has a smooth gradation of effective properties in the radial direction. Therefore, we deal here with a special case of functionally graded materials, FGM (cf. [6]).
Keywords: przewodnictwo cieplne; niestacjonarny przepływ ciepła; kompozyt; heat conduction; FGM; composite